The pernicious “marihuanazo” - Nizama V., Martín (2014)
Marijuana is the most consumed illegal drug in the world and the one with the most frequent initiation is a powerful inducer of the use of other legal and illegal substances. Legalization of marijuana, does not separate it or individualize it from the general drug market, nor release it from the illegal drug underworld, in which alcohol and snuff coexist, among other drugs. It should be noted that legalization of alcohol and snuff did not decrease production and consumption of these substances; on the contrary they expanded to the point that they are currently the most widely consumed drugs in the global society. Proponents of marijuana legalization lie when they say it will decrease their consumption. Marijuana addicts buy the most powerful one and they do not care if it is the government or the provider (dealer) who sells it. Illegal marijuana growers will produce higher potency marijuana, while the government cannot compete in this area. Acute and chronic consumption injure brain structures and disrupts neural circuits, causing deterioration of the personality with withdrawal of personal, family and social roles, so we must ask ourselves: Is it ethical for the government to legalize marijuana?